(untitled) - Buckett, Maurice (Oxford, 1981)
The interval between the first and second editions of this book have witnessed significant changes for the food producers of the EEC. They have moved from a period of increasing production to an era of food surpluses and statutory reductions in production. This overall change in the fortunes of agriculture have greatly increased the need for sound business management. This book has been substantially updated to include all the current factors that have to be taken into consideration by farmers, as well as still providing a basic introduction to the study of farm management for students. It should prove invaluable reading to those running farms, whether experienced or inexperienced.
Keywords: Farm management,Quản lý nông trại